Pain intensity in cluster headache - case report - Souza, Sofia Gameiro de; Jorge, Rodrigo Amorim; Souza, Jano Alves de; Neto, Raimundo Marcial de Brito; Nimer, Gabriela Flor (Headache Medicine, 2023)
Full abstract in PDF.